The impact of COVID-19 post-infection on the cognition of adults from Peru - Zegarra-Valdivia, Jonathan; Arana-Nombera, Harold; Perez-Fernandez, Leandro; Alamo-Medina, Reyna; Casimiro, Milagros del Rocío; Bustamante-Delgado, Diana; Matallana-Sanchez, Maribel; Gallegos-Manayay, Viviana; Álvarez-Bravo, Elizabeth; Arteaga-Cancino, Tihany; Abanto-Saldaña, Eduardo; Oliva-Piscoya, María del Rosario; et al. (Frontiers in Psychology, 2024)
The COVID-19 pandemic, with over 83 million confirmed cases and 1.8 million deaths, has raised concerns about long-term cognitive issues, especially in populations facing disparities. Despite a few years since Peru's first COVID-19 wave, the cognitive effects on adults remain unclear. This study is the first in Peru to explore COVID-19's impact on general cognition and executive function.A retrospective cross-sectional study compared individuals with COVID-19 history to controls, assessing general cognition, verbal fluency, attention, and executive function. Among 240 assessed, 154 met the study inclusion criteria, with about 60% female and an average age of 38.89 ± 16.001 years. Groups included controls (n=42), acute phase (AP, n =74) (1-14 days of symptoms), and hyperinflammatory phase (HP, n =38) (>14 days of symptoms).RESULTS: Significant cognitive differences were observed. The HP group exhibited lower general cognitive performance (p= 0.02), working memory (p=0.01), and executive function (planning; p< 0.001; flexibility; p=0.03) than controls. Those with <14 days of illness (AP vs. HP) had deficits in general cognitive performance (p=0.02), working memory (p=0.02), and planning (p< 0.001), mainly during the hyperinflammatory phase, showing differences in working memory (p= 0.003) and planning (p=0.01). Gender differences emerged, with males in the HP phase having poorer working memory (p=0.003) and planning (p=0.01).DISCUSSION: This study underscores COVID-19's negative impact on cognitive function, even in mild cases, with potential heightened effects in men during acute or hyperinflammatory phases. The findings provide Peru's first evidence, highlighting the vulnerability of populations facing socioeconomic disparities.